Patterns in reporting and participant inclusion related to race and ethnicity in autism intervention literature: Data from a large-scale systematic review of evidence-based practices. (November 2022) - Steinbrenner, Jessica R; McIntyre, Nancy; Rentschler, Lindsay F; Pearson, Jamie N; Luelmo, Paul; Jaramillo, Maria Elizabeth; Boyd, Brian A; Wong, Connie; Nowell, Sallie W; Odom, Samuel L; Hume, Kara A
There are marked racial and ethnic disparities in diagnosis and services for individuals on the autism spectrum, yet race and ethnicity are underreported and underexamined in autism research. The current study examines the reporting of race and ethnicity and the inclusion of participants across racial and ethnic groups in studies included in a large-scale systematic review of autism intervention research (1990–2017). Trained research assistants reviewed 1013 articles and extracted data on the reporting of race and ethnicity data and the inclusion of participants from different racial and ethnic categories from each article. Only 25% of the articles reported any data on race and ethnicity and reporting over time has slowly increased across the 28 years of the review. Descriptive statistics suggest that race and ethnicity reporting varied by study design, intervention, and outcomes. In studies with reported data, White participants had the highest rate of participation (64.8%), with a large gap between the next highest rates of participation, which were among Hispanic/Latino (9.4%), Black (7.7%), and Asian (6.4%) participants. The lack of reporting and the limited inclusion of participants across minoritized racial and ethnic groups are concerning and suggest a need to examine practices in autism research from planning to dissemination. Lay Abstract: Researchers who study autism-related interventions do a poor job reporting data related to the race and ethnicity of autistic individuals who participate in their studies, and of those who do report these data, the participants are overwhelmingly White. This is problematic for many reasons, as we know little about how interventions are meeting the needs of culturally and linguistically diverse populations, and we assume that interventions are effective for all when they have been developed and validated primarily with and for White children. This study examined the reporting patterns of autism intervention researchers whose work was included in a large-scale systematic review of the intervention literature published between 1990 and 2017. We found that only 25% of studies (out of 1, 013 included in the review) included data related to the race and ethnicity of their participants, with minimal change in reporting patterns across the years. In studies with reported data, White participants had the highest rate of participation, with a large gap between the next highest rates of participation among Hispanic/Latino, Black, and Asian participants. Other race and ethnicity groups had very low representation. This study includes additional analyses which examine how the reporting patterns and the inclusion of racially and ethnically diverse participants varies across study types, interventions, and outcome areas. Reporting this data is merely a starting point to begin to address the many disparities in autism-related healthcare, education, and research practices, and this article includes broader implications and next steps to ensure the field becomes more equitable and inclusive.